2002
DOI: 10.1002/1521-4079(200209)37:9<964::aid-crat964>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vacuum Evaporated Polycrystalline Cd0.96Zn0.04Te Thin Films by XRD, Raman Scattering and Spectroscopic Ellipsometry

Abstract: Cd0.96Zn0.04Te thin films are deposited onto well cleaned glass substrates (Corning 7059) kept at room temperature by vacuum evaporation and the films are annealed at 423 K. Rutherford Backscattering Spectrometry and X‐ray diffraction techniques are used to determine the thickness, composition and crystalline structure and grain size of the films respectively. The films exhibited zinc blende structure with predominant (111) orientation. The surface morphology of the films is studied by Atomic Force Microscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Figure 2 shows the crystallite size of the CdS thin films as a function of the film thickness. It initially increases as the film thickness increases, and it is nearly constant If the crystallite size is known, the dislocation density δ of the CdS thin film is determined using the relation [16]: (2) where D is the crystallite size of the CdS thin film. Figure 3 shows the dislocation density of the CdS thin films as a function of the deposition time.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the crystallite size of the CdS thin films as a function of the film thickness. It initially increases as the film thickness increases, and it is nearly constant If the crystallite size is known, the dislocation density δ of the CdS thin film is determined using the relation [16]: (2) where D is the crystallite size of the CdS thin film. Figure 3 shows the dislocation density of the CdS thin films as a function of the deposition time.…”
Section: Resultsmentioning
confidence: 99%
“…Spectroscopic ellipsometry (SE) is a useful and nondestructive tool to obtain the optical constants of thin films. The complex dielectric function, optical constants, and microstructure of thin films are studied from spectroscopic ellipsometry [6,9,10,[18][19][20][21]. The optical constants of refractive index, extinction coefficient, normal-incidence reflectivity, and absorption coefficient in thin films are obtained using SE data of the complex dielectric function [18,19,22].…”
Section: Introductionmentioning
confidence: 87%
“…The complex dielectric function, optical constants, and microstructure of thin films are studied from spectroscopic ellipsometry [6,9,10,[18][19][20][21]. The optical constants of refractive index, extinction coefficient, normal-incidence reflectivity, and absorption coefficient in thin films are obtained using SE data of the complex dielectric function [18,19,22]. The dispersion of refractive index can be analyzed using the WempleDiDomenico single-oscillator model (W-D model) [23], in which the refractive index n in the low absorption region is expressed using the oscillator energy, dispersion energy, and photon energy.…”
Section: Introductionmentioning
confidence: 99%
“…From the table it has been observed that the grain size increases with increase in thickness whereas the strain and the dislocation density decrease with the increase in thickness. Due to the increase in grain size with film thickness, the defects in the lattice are decreased, which in turn reduce the internal micro strain and dislocation density/or the columnar grain growth is increased [18].…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%